Electroluminescent and Optoelectronic Properties of OLEDs with Bay‐Extended, Distorted Perylene Esters as Emitter Materials. Issue 15 (6th June 2017) - Vollbrecht, Joachim; Blazy, Simon; Dierks, Philipp; Peurifoy, Samuel; Bock, Harald; Kitzerow, Heinz
Abstract: Three esters with a perylene, a unilaterally, and a bilaterally extended perylene core, respectively, were used as emitter materials for organic light‐emitting diodes. The electroluminescent properties of these devices were studied. Different spectral shifts were found, which can be attributed to the formation of excited dimers (excimers) in the nanofilms of the emitter materials. Thermal treatment of the unilaterally extended derivative resulted in a red‐shift of the electroluminescence owing to the formation of a denser nanofilm. The luminance and efficiency of optoelectronic devices employing the extended perylene esters exceed those of devices using an emitter layer comprised of the perylene ester. Different deposition methods, limitations in the deposition process, and the role of hole‐transporting materials are compared. Abstract : Different perylene derivatives are tested as emitter materials in organic light‐emitting diodes. After thermal treatment, the emission can be altered due to the formation of a denser packed nanofilm. This behavior can be explained by the formation of excited dimers and is in agreement with prior studies.